Economic evaluation of a hypothetical screening assay for alloimmunization risk among transfused patients with sickle cell disease. Issue 8 (27th February 2014) - Kacker, Seema; Ness, Paul M.; Savage, William J.; Frick, Kevin D.; Shirey, R. Sue; King, Karen E.; Tobian, Aaron A.R.
<x xml:space="preserve">Abstract</x> Background Prophylactic antigen‐matching can reduce alloimmunization rates among chronically transfused patients with sickle cell disease (SCD), but this matching increases costs and may only benefit 30% of patients. We assessed the clinical and financial value of a potential assay for alloimmunization risk that would allow for targeted antigen‐matching. Study Design and Methods A Markov‐based model evaluated direct medical costs and alloimmunization events over 10 to 20 years among transfused (simple or exchange) patients with SCD. Four matching strategies were evaluated: prospective matching (for all patients), history‐based matching (only for patients with prior alloimmunization), perfectly informed matching (assay with 100% sensitivity, 100% specificity), and imperfectly informed matching (reduced accuracy). Under all matching protocols, matching included C, E, K, and any additional alloantibodies present. A hospital perspective was adopted, with costs (2012US) and events discounted (3%). Results Perfectly informed antigen‐matching using a 1000 assay is expected to save 82, 334 per patient over 10 years, compared to prospective matching. Perfectly informed antigen‐matching is more costly than history‐based matching, but reduces alloimmunization events by 45.6% over 10 years. Averting each alloimmunization event using this strategy would cost an additional 10, 934 per patient. Imperfectly informed antigen‐matching using an assay with 75% specificity and 75% sensitivity is less costly than prospective matching, but increases alloimmunization events. Compared to history‐based matching, imperfectly informed matching would decrease alloimmunization events by 32.61%, at an additional cost of 147, 915 per patient over 10 years. Cost‐effectiveness of informed antigen‐matching is largely driven by assay specificity. Conclusions A sufficiently specific assay to inform antigen‐matching may be cost‐effective in reducing alloimmunization among transfused patients with SCD.